Short-Term Impact of COVID-19 on Consumption and Labor Market Outcomes: Evidence from Singapore - Seonghoon Kim; Kanghyock Koh; Xuan Zhang (Institute of Labor Economics (IZA), 2020)
We examine the short-term impact of COVID-19 on consumption spending and labor market outcomes. Using monthly panel data of individuals mainly aged 50–70 in Singapore, we find that COVID-19 reduced consumption spending and labor market outcomes immediately after its outbreak, and its negative impact quickly evolved. At its peak, the pandemic reduced total household consumption spending by 22.8% and labor income by 5.9% in April. Probability of full-time work also went down by 1.2 pp and 6.0 pp in April and May, respectively, but employment and self-employment were only mildly affected. Our heterogeneity analysis indicates that the reduction in consumption spending was greater among those with higher net worth, while the decreases in labor market outcomes were greater among those with lower net worth. However, we find little evidence that those in worse health status experienced larger reductions in consumption spending and labor market outcomes. Reductions in consumption spending correlated with increased risk avoidance behavior, the nationwide partial lockdown, worsening economic outlook, and reduced income.
Keywords: E2; I12; H2; J01; 330; COVID-19; pandemic; consumption spending; labor market; monthly panel data